PROSPEK DAN TANTANGAN INDUSTRI PENERBITAN JURNAL DAN PROSIDING MELALUI TEKNOLOGI E-PUBLISHING DI ERA DIGITAL - Purwadi, Purwadi; Irwansyah (Direktorat Repositori, Multimedia, dan Penerbitan Ilmiah - Badan Riset dan Inovasi Nasional (BRIN Publishing), 2020)
This study aims to determine: (1) the publication of journals and proceedings using e-publishing technology; (2) the prospect of the industry in publishing journals and proceedings in the digital era in the Indonesian context; (3) challenges and efforts to disseminate e-journal and e-proceeding. The study approach is qualitative with the literature review method. The results of the study show that: (1) the use of e-publishing technology is an important part of the publication of e-journal and e-proceeding in the future, which is more flexible, efficient and effective than before; (2) the prospect of publishing the journal and proceedings in the future is fairly bright because publishing technology is more sophisticated, so it encourages better publishing products in terms of types and numbers that are increasingly numerous, interactive, easily accessible, utilizing artificial intelligence, until finally all archiving has made use of big data; (3) the challenges in publishing journals and online proceedings are the competence of human resources, many competitors in this business, the quality of publications tend to be ignored, the disruption of professions, and many abrupt publishers. Meanwhile, digital technology has made the dissemination of journals and proceedings easier, faster and more efficient because they do not involve many parties anymore. E-publishing also reduces the bureaucracy of publishing journals and proceedings, such as not requiring printed correspondence, but simply through e-mail or tools in OJS or OCS applications.